Recognition of the flood- and earthquake-induced deposits in Qionghai Lake: implications for the quantitative analysis of abnormal lacustrine sediments - Li, Yingying; Li, Linlin; Li, Quan; Li, Dewen; Jiang, Yuquan (Frontiers in Earth Science, 2025)
Lake sediments are an important carrier for recording natural disaster events. The key lies in correctly identifying the causes of abnormal lacustrine sediments. The study area, Qionghai Lake, is located at the southeastern edge of the Tibetan Plateau, at the junction of the Anning River Fault and the Zemu River Fault. Disasters such as earthquakes and floods are quite common. By conducting high-resolution analyses of chronology, sedimentary structure, and physical and chemical indicators on six short sediment cores collected from Qionghai Lake, we find that the common characteristics of flood- and earthquake-induced deposits are a sudden increase in the mean grain size, poor sorting property, and an abnormally high Mn content at the bottom of some event layers. The differential characteristics of earthquake-induced deposits are: that the contents of terrigenous elements such as Si and Rb remain at a relatively stable level; that the sedimentary structure lacks obvious bedding and is a homogeneous layer; and that the grain-size characteristics of some event layers show oscillatory changes. The differential characteristics of flood-induced deposits are a significant increase in the contents of indicator elements of terrigenous clastic sediments; and a gradually decreasing grain-size trend upwards, showing an obvious normal grading feature. In addition, the calculation of seismic intensity for earthquakes around Qionghai Lake shows that the threshold for seismically-induced deposit response in Qionghai Lake should be between 4.44–5.95 MMI.